Soccer increases bone mass in prepubescent boys during growth: a 3-yr longitudinal study - Zouch, M.; Zribi, A.; Alexandre, C.; Chaari, H.; Frere, D.; Tabka, Z.; Vico, L. (Journal of Clinical Densitometry, 2015)
The aim of this study was to examine the effect of 3-yr soccer practice on bone acquisition in prepubescent boys. We investigated 65 boys (aged 10-13 yr, Tanner stage I) at baseline, among which only 40 boys (Tanner stages II and III) have continued the 3-yr follow-up: 23 soccer players (F) completed 2-5 h of training plus 1 competition game per week and 17 controls (C). Bone mineral density (BMD, g/cm2) and bone mineral content (BMC, g) were measured by dual-energy X-ray absorptiometry at different sites. At baseline, BMD was higher in soccer players than in controls in the whole body and legs. In contrast, there was nonsignificant difference BMD in head, femoral neck, arms, and BMC in all measured sites between groups. At 3-yr follow-up, soccer players were found to have higher BMD and BMC at all sites than controls, except for head BMD and BMC and arms BMC in which the difference was nonsignificant between groups. During the 3-yr follow-up, the soccer players were found to gain significantly more in lumbar spine (31.2% ± 2.9% vs 23.9% ± 2.1%; p < 0.05), femoral neck (24.1% ± 1.8% vs 11.4% ± 1.9%; p < 0.001), whole body (16.5% ± 1.4% vs 11.8% ± 1.5%; p < 0.05), and nondominant arm BMD (18.2% ± 1.4% vs 13.6% ± 1.7%; p < 0.05) as well as lumbar spine (62.5% ± 20.1% vs 39.5% ± 20.1%; p < 0.001), femoral neck, (37.7% ± 14.2% vs 28.9% ± 12.8%; p < 0.05) and nondominant arm BMC (68.6% ± 22.9% vs 50.1% ± 22.4%; p < 0.05) than controls. In contrast, soccer players have less %BMD and %BMC changes in the head than controls. A nonsignificant difference was found in legs, dominant arm, head %BMD and %BMC changes, and whole-body %BMC changes between groups. In summary, we suggest that soccer has an osteogenic effect BMD and BMC in loaded sites in pubertal soccer players. The increased bone mass induced by soccer training in the stressed sites was associated to a decreased skull bone mass after 3 yr of follow-up.